The effect of leverage, managerial ownership, and profitability on company value (Lighthouse Publishing, 2022)
This study examines the effect of leverage, managerial ownership, and profitability on firm value and size as control variables. The sample in this study is manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange from 2016-2020. This study's method of determining the sample used purposive sampling and multiple linear regression analysis as analytical tools. This study uses five independent variables to achieve these objectives: leverage, managerial ownership, and profitability, with the dependent variable being firm value and firm size as control variables. This research was conducted by directing quantitative methods with secondary data. This secondary data is taken from financial reports downloaded from the Indonesia Stock Exchange website. The results of this study prove that Leverage and Profitability have a significant positive effect on firm value in manufacturing companies in the consumer goods industry sector. However, managerial ownership does not significantly affect firm value in manufacturing companies in the consumer goods sector. The limitation of this study is that it uses a limited sample of manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange from 2016-2020, while there are still many other sectors that are not used in this study.